Search for decays of stopped, long-lived particles from 7 TeV pp collisions with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbia, E; Acharya, B; et al. (2012)
New metastable massive particles with electric and colour charge are features of many theories beyond the Standard Model. A search is performed for long-lived gluino-based R-hadrons with the ATLAS detector at the LHC using a data sample corresponding to an integrated luminosity of 31 pb-1. We search for evidence of particles that have come to rest in the ATLAS detector and decay at some later time during the periods in the LHC bunch structure without proton-proton collisions. No significant deviations from the expected backgrounds are observed, and a cross-section limit is set. It can be interpreted as excluding gluino-based R-hadrons with masses less than 341 GeV at the 95 % C. L., for lifetimes from 10-5 to 103 seconds and a neutralino mass of 100 GeV. © 2012 CERN for the benefit of the ATLAS collaboration.